Normative data for rotational chair considering motion susceptibility - Yu, Jiaodan; Wan, Yi; Zhao, Jieli; Huang, Ruonan; Wu, Peixia; Li, Wenyan (Frontiers in Neurology, 2022)
Objective: Rotational Chair Test (RCT) is considered one of the most critical measures for vestibular functionality, which generally includes the sinusoidal harmonic acceleration test (SHAT), velocity step test (VST), and visual suppression (VS). The purpose of this study was to establish normal values for different age groups on the RCT and investigate whether motion susceptibility, such as with a history of motion sickness or migraine, has any effects on test metrics. Methods: One hundred and nine subjects aged from 20 to 59 years who were free from neurotological and vestibular disorders were enrolled. According to the history of motion sickness or migraine, participants were divided into four groups: the motion sickness (MS) group (n=13), the migraine group (n=8), comorbidity group (n=11) and the control group (n=77). The 77 subjects without any history of MS and migraine were then further separated into four age groups: youth group (20-29 years), young and middle-aged group (30-39 years), middle-age group (40-49 years), and middle-age and elderly group (50-59 years). All participants underwent SHAT, VST, and VS, and a comprehensive set of metrics including gain, phase, asymmetry, time constant (TC), and Fixation Index were recorded. Results: Regarding the VST and VS, no significant differences were observed either across the four groups (MS, migraine, comorbidity and control group) or four age categories within the control group. For SHAT, VOR gain at the frequency of 0.01 Hz, VOR phase from 0.08 to 0.64 Hz, and asymmetry at 0.01, 0.16, and 0.64 Hz indicated significant differences among various age groups (P<0.05 for all comparisons). The VOR phase lead was lower in the migraine and comorbidity group than that in the control group at 0.64 Hz (P=0.027, P=0.003, respectively). Conclusions: Age slightly affects the result of SHAT, but not for VST and VS. VOR gain is more susceptible to aging at low frequency, while the phase is opposite. Subjects with both migraine and motion sickness show abnormal velocity storage mechanisms. Phase bias should be considered when assessing motion susceptibility with the RCT. SHAT is more sensitive than VST in terms of reflecting motion susceptibility.